A novel reversible fluorescent probe based on naphthalimide for sequential detection of aluminum (Al3+) and fluoride (F−) ions and its applications. Issue 44 (3rd November 2021) - Zhang, Shanzhu; Gu, Yunlan; Shi, Zongqian; Lu, Nan; Xu, Haiyan
Abstract : A novel fluorogenic "off–on–off" probe NBP was prepared for sequential detection of Al 3+ and F − ions. The practical applications of this designed NBP were found that it could be successfully used for the biological imaging and test strips. Abstract : A new Schiff base fluorescent probe NBP derived from the one-step condensation strategy of 2-butyl-6-hydroxy-1, 3-dioxo-2, 3-dihydro-1 H -benzo[ de ]isoquinoline-5-carbaldehyde and N -(2-(hydrazinecarbonyl)phenyl)benzamide was synthesized and characterized. NBP exhibited high selectivity toward Al 3+ along with naked-eye color changes and prominent fluorescence enhancement. The limit of detection (LOD) of NBP toward Al 3+ was detected to be 80 nM. The binding ratio of NBP with Al 3+ ions was obtained as 1 : 2 on the basis of Job's plot with the association constant K a value of 4.22 × 10 10 M −1/2 . The plausible complexation mechanism of NBP toward Al 3+ ions was validated by the density functional theory (DFT) and IR spectrum. In addition, in situ formed "NBP + Al 3+ " could be utilized as the second sensor for selective recognition of F − via fluorescence quenching with a low detection limit (44 nM). Furthermore, the cell imaging experiments of probe NBP in HeLa cells have successfully demonstrated that NBP could serve as an indicator for monitoring Al 3+ ions in living cells. On top of that, NBP could be used to prepare simple test paper strips for quickly and qualitatively detecting a trace amount of Al 3+ ions in a visible manner.